PROMOTING OF SELF-DIRECTED LEARNING IN COOPERATION WITH THE PARENTS FOR CHILDREN IN THE PRESCHOOL AGE - Vanaga, Asja; Rutka, Lūcija (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2015)
Successful learning process in pre-school requires collaboration between children, educators and parents, whose primary goal is individual understanding of each child to promote his academic performance and personal development as a whole. This paper shows a pre-scientific and theoretical background of self-directed learning in preschool, as well as developed and theoretically substantiated child initiative research method "New friend". Particular attention is given to the promotion of the child's initiative, which is crucial in the process of self-directed learning. The empirical study of children's initiatives shows analysis of collaboration with the parents. A qualitative study reveals pre-school children's initiative promotion opportunities in collaboration with parents, by using research method "New friend".